An observational study of sleep characteristics in elite endurance athletes during an altitude training camp at 1800 m - Hrozanova, M.; Talsnes, R.; Karlsson, Ø.; McGawley, K.; Moen, F. (Sleep Health, 2021)
Objectives: To observe changes in sleep from baseline and during an altitude training camp in elite endurance athletes. Design: Prospective, observational. Setting: Baseline monitoring at <500 m for 2 weeks and altitude monitoring at 1800 m for 17-22 days. Participants: Thirty-three senior national-team endurance athletes (mean age 25.8 ± S.D. 2.8 years, 16 women). Measurements: Daily measurements of sleep (using a microwave Doppler radar at baseline and altitude), oxygen saturation (SpO2), training load and subjective recovery (at altitude). Results: At altitude vs. baseline, sleep duration (P = .036) and light sleep (P < .001) decreased, while deep sleep (P < .001) and respiration rate (P = .020) increased. During the first altitude week vs. baseline, deep sleep increased (P = .001). During the first vs. the second and third altitude weeks, time in bed (P = .005), sleep duration (P = .001), and light sleep (P < .001) decreased. Generally, increased SpO2 was associated with increased deep sleep while increased training load was associated with increased respiration rate. Conclusion: This is the first study to document changes in sleep from near-sea-level baseline and during a training camp at 1800 m in elite endurance athletes. Ascending to altitude reduced total sleep time and light sleep, while deep sleep and respiration rate increased. SpO2 and training load at altitude were associated with these responses. This research informs our understanding of the changes in sleep occurring in elite endurance athletes attending training camps at competition altitudes.